Assessment of Anger-Related Cognitions of People with Intellectual Disabilities. Issue 5 (28th March 2016) - Richardson, Charlotte; Killeen, Stewart; Jahoda, Andrew; Christopher, Rose; Rose, John; Willner, Paul
Abstract : Background: Interventions for anger represent the largest body of research on the adaptation of cognitive behavioural therapy (CBT) for people with intellectual disabilities. The extent to which the effectiveness of these interventions reflects the behavioural or cognitive components of CBT is uncertain. This arises in part because there are few measures of anger-related cognitions.Method: The Profile of Anger-related Cognitions (PAC) is built around interpersonal scenarios that the participant identifies as personally anger-provoking, and was designed as an extension of the Profile of Anger Coping Skills (PACS). A conversational presentational style is used to approach ratings of anger experienced in those situations and of four relevant cognitive dimensions: attribution of hostile intent, unfairness, victimhood, and helplessness. The PAC, and other measures, including the PACS, was administered to (i) people with ID identified as having problems with anger control ( n = 12) and (ii) university students ( n = 23); its psychometric properties were investigated and content analyses were conducted of participants' verbal responses. In a third study, clinicians ( n = 6) were surveyed for their impression of using the PAC in the assessment of clients referred for help with anger problems.Results: The PAC had good consistency and test-retest reliability, and the total score on the four cognitive dimensions correlated significantly with anger ratings but not with impersonal measures of anger disposition. The predominant cognitions reported were perceptions of unfairness and helplessness. People with ID and university students were in most respects very similar in both the psychometric analyses and the content analyses of their verbal responses. The PAC had high acceptability both to people with ID and to clinicians.Conclusions: The PAC may be a useful instrument for both clinical and research purposes. Personal relevance and the conversational mode of administration are particular strengths.